Phân tích yếu tố ảnh hưởng đến quyết định làm việc trái ngành và trái trình độ: Trường hợp nghiên cứu tại Việt Nam - Nguyễn Ngọc Hà, Trân (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
The rapid expansion in the number of universities and colleges in Vietnam in two recent decades leads to an unbalance in the labour market. However, there is little attention has been given to investigating job mismatches in Vietnam. By using data from our own survey conducted in 2019, the author discussed the factors that affect the odds of job mismatch. Result reveals that age, non-employment income, immigration status, and grade at high school are important determinants of vertical mismatch. The author also found that number of dependents, spouse’s income, schooling year, and characteristics of study programs affect the risk of horizontal mismatch.
Keywords: Job mismatch; Under-education; Over-education; Vertical mismatch. Horizontal mismatch